2004
DOI: 10.1002/hep.20280
|View full text |Cite
|
Sign up to set email alerts
|

Beyond insulin resistance in NASH: TNF-? or adiponectin?

Abstract: Adiponectin has antilipogenic and anti-inflammatory effects, while tumor necrosis factor ␣ (TNF-␣) reduces insulin sensitivity and has proinflammatory effects. We examined (1) the extent to which hypoadiponectinemia and TNF-␣ activation are features of nonalcoholic steatohepatitis (NASH) and (2) whether serum levels of these markers correlate with the severity of histological changes in 109 subjects with nonalcoholic fatty liver disease (NAFLD), including 80 with NASH and 29 with simple steatosis. By multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
702
11
29

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 908 publications
(795 citation statements)
references
References 56 publications
43
702
11
29
Order By: Relevance
“…Our findings showed the existence of a close link between HCV infection and metabolic abnormalities. We found that HCV infection was positively correlated with serum adiponectin level, which was different from previously reports on subjects with non-alcoholic steatohepatitis (NASH) [20,33].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings showed the existence of a close link between HCV infection and metabolic abnormalities. We found that HCV infection was positively correlated with serum adiponectin level, which was different from previously reports on subjects with non-alcoholic steatohepatitis (NASH) [20,33].…”
Section: Discussioncontrasting
confidence: 99%
“…Adiponectin, an adipokine, has been implicated in the pathogenesis of type 2 diabetes mellitus and nonalcoholic fatty liver disease (NAFLD), and appears to have many favorable effects on glucose and lipid metabolism [20,21]. It is positively correlated with insulin sensitivity and is decreased in obese and type 2 diabetic patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NAFLD exhibit reduced adiponectin levels, which are inversely correlated with the severity of NAFLD histology [59]. The reduced production of adiponectin associated with obesity may contribute to the progression of NAFLD [46,56,59] and CVD [60], since this hormone appears to exert strong anti-inflammatory and anti-fibrotic effects. In contrast, leptin levels are increased in NAFLD, and may play a role in the progression from pure steatosis to NASH, at least according to studies in animal models [46,56].…”
Section: Biological Mechanisms Potentially Responsible For Acceleratementioning
confidence: 99%
“…It is unclear how the 'second hit' leads to the development of progressive liver disease, although oxidative stress and pro-inflammatory cytokines have been implicated. [56][57][58] The nature of these 'hits' is unknown.…”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%
“…61 Serum and hepatic adiponectin levels are lower in patients with NASH than in those with simple steatotsis. 56,62 It has also been shown that exogenous adiponectin reverses experimental NAFLD and NASH, potentially via peroxisome proliferator-activated receptor-a (PPAR-a). 63 This is supported by evidence that thiazolidinediones (which are PPAR-g agonists) stimulate adiponectin synthesis and are a potential therapeutic agent in fatty liver disease.…”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%